Skip to content
Related Articles

Related Articles

Improve Article

Sum of alternating sign cubes of first N Natural numbers

  • Last Updated : 24 Mar, 2021
Geek Week

Given a number N, the task is to find the sum of alternating sign cubes of first N natural numbers, i.e., 
 

13 – 23 + 33 – 43 + 53 – 63 + …. 
 

Examples: 
 

Input: N = 2 
Output: -7 
Explanation: 
Required sum = 13 – 23 = -7
Input: N = 3 
Output: 20 
Explanation: 
Required sum = 13 – 23 + 33 = 20 
 

 



Naive Approach: A simple solution is to solve this problem by iterating over a loop from to N and compute the sum by alternating the sign each time.
Below is the implementation of above approach: 
 

C++




// C++ implementation to compute
// the sum of cubes with
// alternating sign
 
#include <iostream>
 
using namespace std;
 
// Function to compute sum
// of the cubes with
// alternating sign
int summation(int n)
{
    int sum = 0;
    for (int i = 1; i <= n; i++)
        if (i % 2 == 1)
            sum += (i * i * i);
        else
            sum -= (i * i * i);
 
    return sum;
}
 
// Driver code
int main()
{
    int n = 3;
    cout << summation(n);
    return 0;
}

Java




// Java implementation to compute
// the sum of cubes with
// alternating sign
import java.util.*;
 
class GFG {
 
// Function to compute sum
// of the cubes with
// alternating sign
static int summation(int n)
{
    int sum = 0;
     
    for(int i = 1; i <= n; i++)
    {
       if (i % 2 == 1)
           sum += (i * i * i);
       else
           sum -= (i * i * i);
    }
    return sum;
}
 
// Driver code
public static void main(String[] args)
{
    int n = 3;
 
    System.out.println(summation(n));
}
}
 
// This code is contributed by offbeat

Python3




# Python3 implementation to 
# compute the sum of cubes 
# with alternating sign
 
# Function to compute sum
# of the cubes with
# alternating sign
def summation(n):
     
    sum = 0
    for i in range(1, n + 1):
        if i % 2 == 1:
            sum = sum + (i * i * i)
        else:
            sum = sum - (i * i * i)
 
    return sum
 
# Driver code
n = 3
 
print(summation(n))
 
# This code is contributed by ishayadav181

C#




// C# implementation to compute
// the sum of cubes with
// alternating sign
using System;
class GFG{
 
// Function to compute sum
// of the cubes with
// alternating sign
static int summation(int n)
{
    int sum = 0;
     
    for(int i = 1; i <= n; i++)
    {
        if (i % 2 == 1)
            sum += (i * i * i);
        else
            sum -= (i * i * i);
    }
    return sum;
}
 
// Driver code
public static void Main(String[] args)
{
    int n = 3;
 
    Console.WriteLine(summation(n));
}
}
 
// This code is contributed by sapnasingh4991

Javascript




<script>
// JavaScript implementation to compute
// the sum of cubes with
// alternating sign
   
    // Function to compute sum
    // of the cubes with
    // alternating sign
    function summation(n)
    {
        let sum = 0;
        for (let i = 1; i <= n; i++)
            if (i % 2 == 1)
                sum += (i * i * i);
            else
                sum -= (i * i * i);
   
        return sum;
    }
   
    // Driver code
 
    let n = 3;
    document.write(summation(n));
  
// This code is contributed by Surbhi Tyagi
 
</script>
Output: 
20

 

Efficient Approach: The key observation in the problem is that every even number is with a negative sign, that is it used to reduce the overall sum. Therefore if we compute the sum of cubes of even numbers and odd numbers individually, then the overall sum can be computed easily.
 

  • Count of Even or Odd numbers in first N natural numbers 
    => Count(C_o) = \frac{N+1}{2}
    => Count(C_e) = \frac{N}{2}
     
  • Sum of first Even Terms 
    => Sum(S_e) = 2*(C_e*(C_e + 1))^{2}
     
  • Sum of first Odd Terms 
    => Sum(S_o) = C_o^{2} * (2*C_o^{2} - 1)
     
  • Overall Sum 
    => S = S_o - S_e
    => S = C_o^{2} * (2*C_o^{2} - 1) - 2*(C_e*(C_e + 1))^{2}
     

Below is the implementation of above approach:
 

C++




// C++ implementation to compute
// the sum of cubes with
// alternating sign
 
#include <bits/stdc++.h>
using namespace std;
 
// Function to compute sum
// of the cubes with alternating sign
int summation(int N)
{
    int co = (N + 1) / 2;
    int ce = (N) / 2;
    int se = 2 * ((ce * (ce + 1))
                  * (ce * (ce + 1)));
    int so = (co * co)
             * (2 * ((co * co)) - 1);
    return so - se;
}
 
// Driver Code
int main()
{
    int n = 3;
    cout << summation(n);
    return 0;
}

Java




// Java implementation to compute
// the sum of cubes with
// alternating sign
import java.util.*;
 
class GFG{
 
// Function to compute sum
// of the cubes with
// alternating sign
static int summation(int N)
{
    int co = (N + 1) / 2;
    int ce = (N) / 2;
     
    int se = 2 * ((ce * (ce + 1)) *
                  (ce * (ce + 1)));
    int so = (co * co) * (2 * ((co * co)) - 1);
     
    return so - se;
}
 
// Driver code
public static void main(String[] args)
{
    int n = 3;
 
    System.out.println(summation(n));
}
}
 
// This code is contributed by offbeat

Python3




# Python3 implementation to compute
# the sum of cubes with
# alternating sign
 
# Function to compute sum of
# the cubes with alternating sign
def summation(N):
     
    co = (N + 1) / 2
    co = int(co)
     
    ce = N / 2
    ce = int(ce)
     
    se = 2 * ((ce * (ce + 1)) *
              (ce * (ce + 1)))
    so = (co * co) * (2 * (co * co) - 1)
     
    return so - se
 
# Driver Code
n = 3
 
print(summation(n))
 
# This code is contributed by ishayadav181

C#




// C# implementation to compute
// the sum of cubes with
// alternating sign
using System;
 
class GFG{
 
// Function to compute sum
// of the cubes with
// alternating sign
static int summation(int N)
{
    int co = (N + 1) / 2;
    int ce = (N) / 2;
     
    int se = 2 * ((ce * (ce + 1)) *
                  (ce * (ce + 1)));
    int so = (co * co) * (2 * ((co * co)) - 1);
     
    return so - se;
}
 
// Driver code
public static void Main(String[] args)
{
    int n = 3;
 
    Console.WriteLine(summation(n));
}
}
 
// This code is contributed by Rohit_ranjan

Javascript




<script>
// javascript implementation to compute
// the sum of cubes with
// alternating sign
 
// Function to compute sum
// of the cubes with
// alternating sign
function summation(N)
{
    var co = parseInt((N + 1) / 2);
    var ce = parseInt((N) / 2);
     
    var se = 2 * ((ce * (ce + 1)) *
                  (ce * (ce + 1)));
    var so = (co * co) * (2 * ((co * co)) - 1);
     
    return so - se;
}
 
// Driver code
var n = 3;
document.write(summation(n));
 
// This code is contributed by Amit Katiyar
</script>
Output: 
20

 

Attention reader! Don’t stop learning now. Get hold of all the important DSA concepts with the DSA Self Paced Course at a student-friendly price and become industry ready.  To complete your preparation from learning a language to DS Algo and many more,  please refer Complete Interview Preparation Course.

In case you wish to attend live classes with experts, please refer DSA Live Classes for Working Professionals and Competitive Programming Live for Students.




My Personal Notes arrow_drop_up
Recommended Articles
Page :